Cerebral Palsy in Y .P .A. C. (Institution for Crippled Children) Semarang - Soelatin Winarno; Oemar Wirjohatmodjo; Harijono Harijono; Siti Alfinah; Wirawan Wirawan (Paediatrica Indonesiana, 1976)
Thirty-five cases of cerebral palsy patients admitted to the Institution for Crippled Children, Semarang, have been discussed. Diagnosis was made by a team comprising an orthopedic surgeon, a neurologist, a paediatrician, and a psychologist. Treatment performed consisted of muscle relaxant, physiotherapy, and also surgery. Introduction, material arid method of observation, treatment, sex distribution; classification, speech disturbance, mental status, results of treatment, and comparison with the cases in Bombay, form the sequence of this report.